The World Literature and Women’s Voice in Toni Morrison’s The Bluest Eye (1970) and Han Kang’s The Vegetarian (2007) - Indiwara Pandu Widyaningrum (Journal of Language and Literature, 2021)
This study seeks to investigate the women’s voice in the world literature depicted by ethnic female authors from African-American and Korean descent. Gaining international recognition in the world literature, Toni Morrison’s The Bluest Eyes (1970) and Han Kang’s The Vegetarian (2007) reveal different social-cultural conditions about how women are presented in their respective nation. Morrison presents the life of colored women struggling with racial discrimination in the predominant white society. Meanwhile, Kang employs the symbolic food of meat and vegetarianism to reveal the women’s voice against social conformity. Applying écriture feminine or women’s writing in the analysis, both Toni Morrison and Han Kang scrutinize the stereotypical representation of women as passive, obedient, and lacking. In examining the two works, some steps were done: 1) having close reading towards the text to analyze the representation of women; 2) doing the socio-cultural analysis in connection to the women’s voice; 3) drawing the conclusion about the significance of world literature to the women’s voice. This study finds that the world literature has its significant contribution as the windows for global readers to understand women’s issues portrayed in two different nations. Not only to present women’s voice, ethnic female authors such as Toni Morrison and Han Kang indeed share the local culture through their novels. With this condition, the world literature enables to break the barriers of male Western authors as the center by offering room for female writers from non-Western countries.